Desktop publishing activities - Blanc, Iris. (Cincinnati, Ohio : South-Western Educational, 1998)
This book is divided into two parts: Introduction to desktop publishing; and Creating presentation decuments.
Keywords: Desktop publishing; Desktop publishing -- Problems, exercises, etc